Project-Based Learning: Enhancing Efl Students’ Speaking Skill Through Vlog - Fatni Sulani Siregar; Achmad Ramadhan; Ernita Daulay (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The research that has been conducted is entitled “Project Based Learning: Enhancing Efl Students’ Speaking Skill Through Vlog At The Seventh Grade Of Smp It Al Hijrah Deli Serdang”, with the background being that students’ english speaking skills are quite apprehensive and learning activities are still just listening and lecturing. Even though the facilities and infrastructure at the school are very adequate and the capability curriculum to be achieved is higher order thinking (HOT). The methodology in this research is to use quantitative methods with pre test, treatment, and post test design approaches in the experimental class and control class. The population in this study were student of class VII SMP It Al Hijrah. This study used a sample of 2 classes, namely for experimental class as many as 21 student from VII C and the control class as many as 21 students from class VII D. This study used a lottery method with random sampling style to select the sample. The validity processing tool uses the IBM SPSS Statistics Version 29 application. The result of this study revealed that there was a significant influence from the use of PBL through Vlog on students’ speaking skills in SMP. This can be seen from the increase in the result of the test, namely a sig (2-tailed) value of 0.001 < 0.05 or t count (3,139) higher than t table (1,684).